2020
DOI: 10.3390/children7030019
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass Index (FMI) as a Trustworthy Overweight and Obesity Marker in Mexican Pediatric Population

Abstract: Predictive formulas to estimate body composition in children have been explored for some time, to this date, the most accurate obesity diagnostic tool is to determine fat mass. The aim of this study is to establish cutoff points that allow for a precise interpretation of nutritional status using the Fat Mass Index (FMI) in a Mexican pediatric population. A literature review using PubMed and Cochrane databases was made, searching for research articles on childhood obesity that compared BMI, FM percentage, and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The FM% also showed an important limit particularly in the case of monitoring the change of the fat mass proportion, which is due to its direct association to the fat free mass compartment. However, FMI seems to be a more realistic index to assess and monitor excess of fat because of its independence from the fat free mass compartment and takes in a count the height [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FM% also showed an important limit particularly in the case of monitoring the change of the fat mass proportion, which is due to its direct association to the fat free mass compartment. However, FMI seems to be a more realistic index to assess and monitor excess of fat because of its independence from the fat free mass compartment and takes in a count the height [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…But several studies confirmed its limitations to determine objectively the extent of obesity in societies [ 11 ]. In addition, it is still a controversy about the ideal indicator to measure overweight or obesity; as many scientists recommend fat mass percentage (FM%) against other authors who have raised its inefficiency as an indicator to determine overweight and obesity, because of its association to the fat free mass compartment variation and does not take account of individual’s size [ 12 , 13 , 14 , 15 ]. However, fat mass index (FMI) seems to be more interesting among the community of scientists and to be more relevant to assess excess of fat and its associations to illness [ 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fat mass index (FMI) was identified as the most reliable index for estimating neonatal adiposity 22 and was calculated from these estimates as previously described 12 . Due to the varying applicability of exponents in body composition indices demonstrated across populations, 23 the specific index used (kg/m 3 ) was confirmed to best describe the relationship between weight and length in the study population by regressing fat mass on length (data in natural logarithms; regression power exponent: 2.8 ± 0.6 [SE]).…”
Section: Methodsmentioning
confidence: 99%
“…Fat mass index (FMI) was identified as the most reliable index for estimating neonatal adiposity 22 and was calculated from these estimates as previously described. 12 Due to the varying applicability of with fetal growth and neonatal size and adiposity.…”
Section: Neonatal Body Compositionmentioning
confidence: 99%
“…FMI is recommended as a more appropriate approach that allows independent evaluation of FM relative to body size (height) [ 23 ]. In addition, recent research has demonstrated that FMI is a more reliable index than %FM when assessing neonatal adiposity [ 48 ]. In contrast, some studies [ 26 , 47 ] have suggested that an appropriate index should adjust the originator of the risk (FM) for a variable that is bearing the risk (FFM), thus recommending the index of FM/FFM p ; however, to the best to our knowledge, only one study [ 26 ] used FM/FFM p to identify maternal predictors of infant adiposity at birth.…”
Section: Discussionmentioning
confidence: 99%